Highway research sharing the benefits : proceedings of the conference The United States Strategic Research Program organized by the Institution of COvili Engineers and held in London on 29-31 October 1990 - Porter, John, 1936 January 30- (Thomas Telford, 1991)
This collection of reports from around the world presents the Strategic Highway Research Program's (SHRP) progress towards providing research-based new products from which the international highway engineering community may benefit.